A Low-Temperature Thermoplastic Anti-bacterial Medical Orthotic Material Made of Shape Memory Polyurethane Ionomer: Influence of Ionic Group - Meng, Q.; Hu, J.; Liu, B.; Zhu, Y.
PCL-based shape memory polyurethane ionomers with quaternarized pyridine moieties incorporated through molecular extension were synthesized. These polyurethanes were specifically designed as lowtemperature thermoplastic anti-bacterial orthotic materials. A commercialized orthotic material was employed for comparison. The influence of ionic groups on the properties of orthotic materials was studied. The anti-bacterial properties and cytotoxicity of the polyurethane ionomer were tested. It was found that, different from other researchers_f conclusions, the Coulombic force among cationic groups and the increased cohesion among hard segments after ionization could lead to polyurethane with better phase separation, soft segment phase crystallability and hard segment phase stability. The results of this work indicated that, although the ionic group had the function of improving phase separation, the asymmetric extender had a negative effect on the hard segment phase stability. Several of the main physical properties of the synthesized polyurethane as orthortic materials were studied. The materials mechanical properties at using temperature (ambient temperature 22.C)were improved so it may be used in circumstances where high mechanical strength is required. The fixity ratio was increased; as a result the material may fix shape more precisely according to patient affected parts. At last, a prototype wrist orthotic device was fabricated by hands. The orthotic device percent reductions against Klebsiella pneumoniae and Staphylococcus aureus were 96.2percent and 100percent, respectively. The anti-bacterial activity rating of this device was acceptable and significant according to ASTM E 2149. Cytotoxicity tests indicated that the wrist orthotic material was not cytotoxic.
Keywords: ORTHOTIC MATERIAL; SHAPE MEMORY POLYURETHANE; IONOMER